The Utilization of Fungi and Their Products to Increase Livestock Production - Ahmad, Riza Zainuddin (Indonesian Animal Sciences Society, 2011)
Fungi as part of eukaryotic organisms play an important role for livestock. Some fungi are detrimental because they cause animal diseases, and some fungi are beneficial because they can improve animal productivity. The use of fungi that benefit from starting he has done as agents of biological control and to be as probiotics.Within the fungi, the use of simple technologies to high level degree for the benefit of cattle is developed. This paper describes some fungi that are beneficial and direction and suggestion to develop research on veterinary micology in Indonesia. Key words: Fungi, mycology, use, animal livestock